1976
DOI: 10.1111/j.1365-2494.1976.tb00780.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fertilizers on the sulphur content of herbage

Abstract: The sulphur concentrations in herbage samples from the plots of a long-term fertilizer experiment have been examined in relation to levels of fertilizers applied. Sulphur applied as superphosphate increased herbage sulphiir concentrations whereas reduction in concentrations were observed with applications of nitrogen as 'Nitro-chalk' and potassium as potassium chloride. Reduction in sulphur concentration occurred most likely as a result of increased dry matter production brought about by the added nitrogen and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…These results are consistent with those of Reith et al (1964) and Whitehead et al (1978), who also found that the effect of fertilizer N outweighed that of KCl. The finding that the higher S concentrations occurred on the No plot at harvest 4 is consistent with results of McLaren (1976) and Whitehead et al (1983).…”
Section: Fertilizer Nsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are consistent with those of Reith et al (1964) and Whitehead et al (1978), who also found that the effect of fertilizer N outweighed that of KCl. The finding that the higher S concentrations occurred on the No plot at harvest 4 is consistent with results of McLaren (1976) and Whitehead et al (1983).…”
Section: Fertilizer Nsupporting
confidence: 92%
“…Increased concentrations of Ca and Mg in summer herbage have been reported elsewhere (Reith et al, 1964;Fleming and Murphy, 1968;Metson and Saunders, 1978). Increases in Na and Mn between spring and summer were reported by Hemingway (1961;1962) and Metson et al (1979), and a higher concentration of S in later cut herbage was noted by McLaren (1976). However, other previous studies have shown little evidence of consistent patterns of seasonal variation with regard to concentrations of Na (Metson and Saunders, 1978;Whitehead etal, 1983), Zn (Reay and Marsh, 1976;Metson et al, 1979) or total S (Whitehead et al, 1983).…”
Section: Seasonal Variationmentioning
confidence: 75%
“…Application of K fertilizer decreased (P = 0.025) S concentrations in first-harvest grass, increased S concentrations in second-and third-harvest grasses (P = 0.014 and 0.008, respectively), and had no effect on S concentrations in fourth-and fifth-harvest grasses (P = 0.351 and 0.122, respectively). McLaren (1976) reported that regardless of harvest, the application of 78 or 314 kg/ha of KCl fertilizer reduced S concentrations in grass, and hypothesized this was attributable to dilution with increasing yield or, second, that S uptake was reduced because of competition for uptake with Cl in the K fertilizer. Roche et al (2002) found that increasing KCl fertilizer application from 0 to 225 kg/ha of K did not affect the S concentration of pastures in either of 2 experiments.…”
Section: K Fertilizermentioning
confidence: 99%
“…These losses are almost certainly due to a combination of plant uptake and leaching. McLaren (1976) observed that, at a site close to the present Midlothian trial even where large amounts of sulphur were applied every year for twenty years, no significant accumulation of sulphur occurred in the soil. This probably occurred because soil organic matter levels remained fairly constant rather than increasing over this period.…”
Section: Soil Sulphatementioning
confidence: 81%